Building Environmental Awareness of the Alpha Generation at SMPN 1 Simpang Pesak Belitung Timur - Dwi Haryadi; Darwance; Aruna Asista (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Efforts to build environmental awareness from an early age are a need today so that in the future a young generation will be born who care and are quick to preserve the surrounding environment. These efforts are carried out by education, socialization and providing examples of good practices. This service activity aims to educate environmental law in accordance with the competence of the proposer team with the target of the alpha generation who are currently in junior high school. Students as the alpha generation are equipped and instilled with awareness of environmental laws from an early age will have a positive impact on environmental sustainability in the future. This service activity provides education from an early age to students of SMP Negeri 1 Simpang Pesak to be concerned and directly involved in protecting the environment through their daily activities such as saving electricity by turning off lights when not in use, using water as necessary, disposing of garbage in its place and reducing the use of plastic. In this activity, the service team also handed over X-banners and stickers to socialize environmental care to the school and tumblers to all participants as a concrete step to reduce plastic waste, so that they no longer use plastic cups/bottles.